2019
DOI: 10.1371/journal.ppat.1008072
|View full text |Cite
|
Sign up to set email alerts
|

Lung transcriptional unresponsiveness and loss of early influenza virus control in infected neonates is prevented by intranasal Lactobacillus rhamnosus GG

Abstract: Respiratory viral infections contribute substantially to global infant losses and disproportionately affect preterm neonates. Using our previously established neonatal murine model of influenza infection, we demonstrate that three-day old mice are exceptionally sensitive to influenza virus infection and exhibit high mortality and viral load. Intranasal pre- and post-treatment of neonatal mice with Lactobacillus rhamnosus GG (LGG), an immune modulator in respiratory viral infection of adult mice and human prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 90 publications
2
45
0
1
Order By: Relevance
“…Sublethal infection with IAV is physiologically relevant because it can closely mimic seasonal influenza infection in humans. In this study, the viral loads can be detected only after 72 h in mice infected with a sublethal dose of IAV were consistent with previous findings, indicating that mild IAV infection was established in these animals [ 60 , 61 ]. We demonstrated that, after infection with a sublethal dose of IAV, mice pre-treated with a combination of heat-killed KB290 and VA had a significantly lower viral load.…”
Section: Discussionsupporting
confidence: 93%
“…Sublethal infection with IAV is physiologically relevant because it can closely mimic seasonal influenza infection in humans. In this study, the viral loads can be detected only after 72 h in mice infected with a sublethal dose of IAV were consistent with previous findings, indicating that mild IAV infection was established in these animals [ 60 , 61 ]. We demonstrated that, after infection with a sublethal dose of IAV, mice pre-treated with a combination of heat-killed KB290 and VA had a significantly lower viral load.…”
Section: Discussionsupporting
confidence: 93%
“…Soil bacteria might therefore improve the biological function of chickens and suppress viral infection or reduce the disease severity as found in human atrophic dermatitis [9] [10] [14]. Indeed, there have been reports that the intake of lactic acid bacteria suppresses the flu virus, suggesting a relationship between the microflora in the digestive tract and immunity: the ingestion of bacteria is thought to activate natural killer (NK) cells, resulting in the suppression of virus infection and relief of symptoms [7] [8]. More detailed cellular and molecular analyses will be required in order to verify the mechanism underlying the ND-suppressive effects of the soil bacterial group BX-1.…”
Section: Discussionmentioning
confidence: 99%
“…A similar, in vivo study on with live and heat-killed Lactobacillus rhamnosus G.G. (LGG) via Intranasal pre-and posttreatment of neonatal mice reveals that an immune modulation in respiratory viral infection significantly improves neonatal mice survival after influenza virus infection [49]. Specifically, upregulates type I IFN pathways ameliorate the symptoms of respiratory viral infection or allergic disease.…”
Section: Arkamentioning
confidence: 94%